Pelatihan Literasi Digital Kepada Siswa SMP Methodist Pematang Siantar - Situmorang, idawati; Sitompul, Hamela Sari; Tuty; Muhammad Sakban (PT. Karya Inovatif Nusantara, 2024)
This Community Service aims to improve digital literacy skills at Pematang Siantar Methodist Middle School. The training participants were students from Pematang Siantar Methodist Middle School. The basic problems of community service activities at Methodist Middle School are: (1) students' digital literacy skills are still low; (2) the literacy motivation of the community, especially students in vocational schools, to improve their competency is still low; and (3) students' understanding in filtering or selecting appropriate literacy content for developing and improving the quality of their science and technology is still lacking. The methods used were: lecture, practice, discussion, question and answer with partners, as well as monitoring and evaluation of the implementation location. The participants in this PKM activity were 30 people who were part of class VIII students of Pematang Siantar Methodist Middle School. The result of this PKM is an increase in students' interest in reading by utilizing digital devices. In addition, students have the ability to recognize and filter positive and negative content available on the internet. Good results were also obtained in developing students' skills in using social media properly, correctly and safely so that students are no longer trapped in accessing content that is not educational or that reduces their creativity.